Perlawanan dan Pembebasan Terhadap Kolonialisme dengan Lensa Poskolonial dalam Novel Jejak Langkah Karya Pramoedya Ananta Toer - Nensilianti, Nensilianti; Ridwan, Ridwan; Pratidina, Nur Ainun (Nuances of Indonesian Language, 2024)
This research focuses on analyzing the novel "Jejak Langkah" by Pramoedya Ananta Toer with a postcolonial approach. Through the descriptive qualitative method, this research explores the resistance and liberation depicted in the main character, Minke, as a representation of the spirit of resistance and aspirations for Indonesian independence. Minke does not only fight physically, but also through intellectual struggle, identity search, and development of political awareness. Through critical writing and relationships with nationalist figures, Minke builds national consciousness among the people and rejects Dutch colonial norms to fight for pride in Indoan identity and culture. This research illustrates the collective struggle to achieve independence and national dignity in the context of colonial colonization.